Differential Hypothalamic-pituitary-adrenal Response to Stress among Rat Strains: Methodological Considerations and Relevance for Neuropsychiatric Research - Armario, Antonio; Belda, Xavier; Gagliano, Humberto; Fuentes, Silvia; Molina, Patricia; Serrano, Sara; Nadal, Roser (Current Neuropharmacology, 2023)
The hormones of the hypothalamic-pituitary-adrenal (HPA) axis, particularly glucocorticoids (GCs), play a critical role in the behavioral and physiological consequences of exposure to stress. For this reason, numerous studies have described differences in HPA function between different rodent strains/lines obtained by genetic selection of certain characteristics not directly related to the HPA axis. These studies have demonstrated a complex and poorly understood relationship between HPA function and certain relevant behavioral characteristics. The present review first remarks important methodological considerations regarding the evaluation and interpretation of resting and stress levels of HPA hormones. Then, it presents works in which differences in HPA function between Lewis and Fischer rats were explored as a model for how to approach other strain comparisons. After that, differences in the HPA axis between classical strain pairs (e.g. High and Low anxiety rats, Roman high- and low-avoidance, Wistar Kyoto versus Spontaneously Hypertensive or other strains, Flinder Sensitive and Flinder Resistant lines) are described. Finally, after discussing the relationship between HPA differences and relevant behavioral traits (anxiety-like and depression-like behavior and coping style), an example for main methodological and interpretative concerns and how to test strain differences is offered.
Keywords: ACTH